2022
DOI: 10.3390/microorganisms10091807
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Japanese Larch Invasion on Soil Bacterial Communities of the Giant Panda Habitat in the Qinling Mountains

Abstract: Japanese larch (Larix kaempferi), a non-native tree species, has been widely planted in the Qinling Mountains since the last century, but it does not meet the habitat needs of giant pandas (Ailuropoda melanoleuca), mainly because of food, further causing habitat degradation and fragmentation. However, how soil microorganisms, considered as predictors of the soil environment, respond to Japanese larch remains poorly explored, especially compared with native forests. Here, we collected 40 soil samples from plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…For example, pine forest communities can easily recruit oligotrophic microorganisms because of the slow decomposition and limited nutrient release of dominant Pinus leaf litter [23,27,28]. Key functional groups involved in mycorrhizal symbiosis and amino-acid metabolism can be strongly affected by shifts in soil nutrient status and forest type [29,30]. Moreover, it has been demonstrated that there is strong competition between ectomycorrhizal (ECM) and saprotrophic fungi for soil resources [31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, pine forest communities can easily recruit oligotrophic microorganisms because of the slow decomposition and limited nutrient release of dominant Pinus leaf litter [23,27,28]. Key functional groups involved in mycorrhizal symbiosis and amino-acid metabolism can be strongly affected by shifts in soil nutrient status and forest type [29,30]. Moreover, it has been demonstrated that there is strong competition between ectomycorrhizal (ECM) and saprotrophic fungi for soil resources [31].…”
Section: Introductionmentioning
confidence: 99%